Mycotic Renal Artery Aneurysm Presenting as Critical Limb Ischemia in Culture-Negative Endocarditis - Vy Thuy Ho; Nathan K. Itoga; Tiffany Wu; Ehab Sorial; Manuel Garcia-Toca (Case Reports in Surgery)
Mycotic renal artery aneurysms are rare and can be difficult to diagnose. Classic symptoms such as hematuria, hypertension, or abdominal pain can be vague or nonexistent. We report a case of a 53-year-old woman with a history of intravenous drug abuse presenting with critical limb ischemia, in which CT angiography identified a mycotic renal aneurysm. This aneurysm tripled in size from 0.46 cm to 1.65 cm in a 3-week interval. Echocardiography demonstrated aortic valve vegetations leading to a diagnosis of culture-negative endocarditis. The patient underwent primary resection and repair of the aneurysm, aortic valve replacement, and left below-knee amputation after bilateral common iliac and left superficial femoral artery stenting. At 1-year follow-up, her serum creatinine is stable and repaired artery remains patent.